2009
DOI: 10.1103/physrevlett.102.082501
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sensitivity of Nuclear Binding Energies to Collective Structure

Abstract: We have studied calculated collective contributions to nuclear binding and separation energies and find that there is a deeper and much more sensitive link to nuclear structure than previously recognized or expected, especially near midshell in medium mass and heavy nuclei. As a consequence, measured masses may help understand the structure of well-deformed nuclei (e.g., intrinsic excitations). Conversely, future structure calculations must consider their implications for binding energies. Nuclear masses and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…1(b). (the other transitions are considered to have E2 character): α = 0.36 (6). This suggests that the 203 keV transition has E2 (α the = 0.37) character.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1(b). (the other transitions are considered to have E2 character): α = 0.36 (6). This suggests that the 203 keV transition has E2 (α the = 0.37) character.…”
mentioning
confidence: 99%
“…The combination of mass and spectroscopic data is essential in understanding the evolution of structure near doubly magic nuclei. Indeed, it has recently been shown that the link between masses and structure is stronger and more sensitive than hitherto thought [6]. Furthermore, because the newly accessible region near 132 Sn [7] shares many similarities with the Pb region, studies…”
mentioning
confidence: 99%
“…These quantities have been recognized as qualified effective order parameters to identify the phase transitions in both eveneven and odd-A nuclei. Furthermore, these quantities only depend on the number of nucleons with abundant experimental data available [2,[4][5][6]. However, through the analysis of these quantities and their odd-even differences [25], it is observed that nearly all the odd-even differences reach their extreme values (maximum or minimum) around the critical point, which, therefore, are more sensitive and suitable to be used as effective order parameters to manifest the shape phase transition.…”
Section: The Nilsson Mean-field Plus Standard Pairing Model and Imentioning
confidence: 99%
“…Quantum phase transitions (QPTs) in nuclei have been analyzed extensively in both experiment and theory [1][2][3][4][5][6]. These studies have provided new insights and understanding of the evolution of nuclear shapes and energy level structures in transitional regions [7].…”
Section: Introductionmentioning
confidence: 99%
“…[2]. It has been shown that ground state masses reveal the structure of excited collective states [3]. Nucleon separation energies are derived from nuclear masses and are a key input for nucleosynthesis calculations [4].…”
Section: Introductionmentioning
confidence: 99%